- 1-800-665-6601
- [email protected]

Here each square root radical should be simplified further.

√4 = √(2 * 2). Now pull out the number which is repeating twice inside the radical.

This gives: √4 = 2and ‘4’ is a perfect square since its square root gives a perfect number!

And we already have

So, √4 * √56 = 2 * 2√14 = 4√14.

Here each square root radical should be simplified further.

√14 = √(2 * 7) and it is already in its simplified form as no number is repeating twice inside the radical to be pulled out.

And we have

So, √14 + √56 = 1√14 +2√14 = (1 + 2) √14 = 3√14.

(They are like terms since they have the same radical √14 and hence can be added).

Hence the value of the expression, √14 + √56 is = 3√14.